LC-MS/MS and Cytotoxic Activity Analysis of Extract and Fraction of Calophyllum soulattri Stembark - Muhamad Salman Fareza; Choironi, Nur Amalia; Susilowati, Sri Sutji; Rini, Melina Puspita; Festihawa, Vyola; Fauzi, Irfansyah Septian Nur; Utami, Esti Dyah; Sarmoko, Sarmoko (Indonesian Journal of Pharmacy, 2021)
Calophyllum soulattri (Sulatri), a plant from Clusiaceae family, has been empirically used as traditional medicine. In the present study, C. soulattri stem bark extract and fractions were evaluated for their toxicity against MCF-7 breast cancer cell. The extract and fraction’s chemical content was analyzed using the combination of liquid chromatography with mass spectrometry (LC-MS/MS). The results showed that methanol extract and n-hexane fractions have strong cytotoxic activity with IC50 values 93.6 and 36 µg/mL, respectively. Meanwhile, as the positive control, ethyl acetate and cisplatin fractions have IC50 values 233 and 16.2 µg/mL, respectively. The LC-MS/MS analysis showed that the extract and fractions contained polyporusterone A, poricoic acid D, polyporusterone F, esulentagenin, and 1-acetyl-3-(methoxy-carbonyl)-β-carboline. Therefore, C. soulattri stem bark extract and fractions have potential activity as an anticancer agent that was able to inhibit MCF-7 breast cancer cell growth.